Comparisons of the QLICP-HN and FACT-H&N instruments for measuring quality of life in patients with head and neck cancer - Shen, Fan; Chi, Wenhua; Yang, Xizi; Li, Gaofeng; Tan, Jianfeng; Wan, Chonghua (Frontiers in Oncology, 2025)
BackgroundTwo head and neck cancer quality-of-life(QoL) measurement tools, the Functional Assessment of Cancer Therapy-Head and Neck (FACT-H&N) and the Quality of Life Instruments for Cancer Patients-Head and Neck Cancer (QLICP-HN), are widely used in China, but several researchers tend to be confused about which QoL measurement tool to choose before conducting QoL measurements. This investigation aimed to employ data procured from patients diagnosed with head and neck cancer to conduct a comparative analysis of these two assessment tools.MethodsQuestionnaire outcomes were scrutinized at the subscale level by utilizing scale measurement analytics, correlation evaluation, validation examination, and association analyses.ResultsCorrelations between the two QoL instruments: the QLICP-HN and the FACT-H&N, fluctuated from r = 0.30 (indicating weak agreement) within the social/family domain to r = 0.80 (indicating robust agreement) within the psychological domain. Intermediate r values were associated with the remaining domains. Examination of typical correlations between the two subscales unveiled a moderate overall concurrence between the two tools (first typical correlation coefficient r = 0.89, although the overall redundancy remained at less than 57%). In the overall measurement performance, each of the two QoL tools exhibited particular strengths. However, the QLICP-HN showcased higher total scale internal consistency coefficients and a more extensive range of subscale internal consistency coefficients than the FACT-H&N scales, albeit it exhibited inferior discriminant and convergent validity.ConclusionThis empirical investigation highlights that, despite some overlap in the information provided by the two QoL instruments, substantial differences persist, thereby negating the possibility of one tool substituting for the other. Consequently, outcomes derived from these two QoL measures cannot be directly juxtaposed.